CATALYST TABLET OF Cu-TiO2/GRAPHITE FOR PHOTO-AND ELECTRO-ASSISTED DEGRADATION OF REMAZOL YELLOW FG - Rahmawati, Fitria; Apriyani, Rochmi I.; Rahardjo, Sentot B. (Alchemy Jurnal Penelitian Kimia, 2012)
Titanium dioxide (TiO2) film was supported on graphite (G) by means of chemical bath deposition (CBD) from TiCl4 precursor. Meanwhile surfactant cetyl trimethyl ammonium bromide (CTAB) was added as linking and assembling agent between titanium network and graphite substrate. Cu was deposited electrochemically from 0.4 M of CuSO4 solution at 0.03 A of electric current. The tablets of TiO2/G and Cu-TiO2/G were used as catalyst for photocatalytic degradation (PC), electrocatalytic degradation (ED) and photoelectrocatalytic (PEC) degradation of Remazol Yellow FG. In degradation system which used TiO2/G tablet, the highest rate constant, k, was achieved by PEC method, k was 2.8ï´10-3 min-1, as well as in the system which used Cu-TiO2/G tablet. However, this research founded that direct oxidation by external electric field contribute more to degradation process than photocatalytic mechanism, proved by high rate constant of ED, k was 2.6ï´10-3 min-1. Meanwhile, rate constant of photocatalytic degradation was 5ï´10-4 min-1. This research also founded that TiO2 film highly contribute in degradation process due to the fact that rate constant of electrodegradation by using blank graphite is low, k was 5ï´10-4 min-1. Meanwhile, deposition of Cu onto TiO2 did not enhance degradation rate of remazol yellow by PEC method, however it enhanced the rate constant of ED to 2.7ï´10-3 min-1. The FTIR analysis to the completedly degraded remazol yellow FG solution shows disappearance of N=N stretching at 1559 cm-1and ïµas CH2 at 2919 cm-1. This indicates that molecular structure of remazol yellow has been degraded succesfully then convert this dye solution into clear solution.Keywords : Cu-TiO2/graphite, electrocatalytic degradation, photoelectrocatalytic degradation, remazol yellow FG, TiO2/Graphite.